(3cJGH GdaUd aj Gdedd hGdBQGA hGdfMds - (3Ydj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe , CHh eMeO ,J (B456 (3g` s ((3GHh GdYHGS CMeO Hf CHj YKeGf SYO Hf CHj LYaQ GHf CMeO GdGfOdSi GdZSGfi s)
(3ChdgG (B:s
(3CeG HYO aEf cKjQkG ef GdfGS cJHhG ai EaJQGb GdfGS ai OjGfGJge hebGdGJge cJH cKjQI LOkG HGH GdcdGe Ydi Cgd GdbSe GdChd hge eHWdhG GdMbGFb hge GdShaSWGFjI s
(3BNQgG (B:s
(3fU BNQ JhGQJge eG Hi GdYGde LedI CMeb ef UaI ef jJeGOi Ydi s
(3GdfSNI HgG MhGTs
(3bWYI efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B319s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds